Attitudes towards participating in research involving digital pill systems to measure oral HIV pre-exposure chemoprophylaxis: a cross-sectional study among men who have sex with men with substance use in the USA. Issue 1 (30th January 2023) - Chai, Peter; De, Dikha; Albrechta, Hannah; Goodman, Georgia R; Takabatake, Koki; Ben-Arieh, Amy; Lee, Jasper S; Glynn, Tiffany R; Mayer, Kenneth; O'Cleirigh, Conall; Fisher, Celia
Abstract : Objectives: This quantitative survey sought to understand, among men who have sex with men (MSM) with potentially problematic substance use, the attitudes towards participation in research involving digital pill systems (DPS) for HIV pre-exposure prophylaxis (PrEP) adherence measurement, and the barriers and facilitators to research participation. Design: One-time, cross-sectional, online sampling-based survey. Setting: US social networking app predominantly focused on MSM. Participants: MSM without HIV who reported current use of oral PrEP, potentially problematic substance use and sexual activity in the past 3 months. A total of 157 participants were eligible, passed validity checks and enrolled. Outcome measures: Perceptions of DPS usefulness, accuracy and usability (System Usability Scale (SUS)); willingness and motivations to participate in DPS research; preferences for access to and feedback on DPS adherence data; data sharing considerations; and medical mistrust (Group-Based Medical Mistrust Scale (GBMMS)). Results: Most of the sample (N=157) was white (n=119, 75.8%), gay (n=124, 79.0%) and cisgender (n=150, 95.5%). The median age was 33 years (IQR: 14). The mean GBMMS score was 13.5 (SD=5.2), and the median SUS score was 70 (IQR: 27.5). In the past 3 months, 36.3% (n=57) reported frequent use of substances before or during sex, and 62.4% (n=98) engaged in condomless sex. While most were adherent to PrEP, approximately 34.4% (n=54) expressed significant worry about daily adherence. Participants wished to monitor their PrEP adherence daily (n=66, 42.0%) and 52% (n=82) were very willing to participate in DPS-based research. The majority were minimally concerned about sharing DPS-detected adherence data with research teams (n=126, 80.3%), and were extremely willing to share these data with healthcare providers (n=109, 69.4%). Conclusions: In this sample, MSM without HIV who use substances reported willingness to use DPS to measure PrEP adherence in a research context, and identified benefits to accessing real-time, DPS-detected adherence data.